A Domain-Specific Language for Multimedia Service Function Chains based on Virtualization of Sensors - Quico, Franklin Jordan Ventura; Battisti, Anselmo L. E.; Muchaluat-Saade, Débora; Delicato, Flavia C. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2024: Proceedings of the 30th Brazilian Symposium on Multimedia and the Web, 2024)
Virtualization is a widely used technology that can abstract the complexity of heterogeneous environments, such as the Internet of Things (IoT) and multimedia systems. Multimedia sensors are an important data source in the Internet of Things (IoT), which brings the Internet of Media Things (IoMT) paradigm. Based on virtualization and IoMT, the concept of a multimedia Virtual Network Function (multimedia VNF) has been adopted to denote the virtualized representation of devices and also software components that process multimedia streams. In many scenarios, multiple processes must be applied to multimedia streams in a predefined sequence, thus creating the concept of multimedia Service Function Chain (multimedia SFC). Few efforts have been made in the literature to create a description language to support the definition of multimedia SFCs. In order to fill this gap, we propose a Domain Specific Language (DSL) called L-PRISM. This DSL can be used as a conceptual base for developers to implement and virtualize multimedia applications using multimedia VNFs. We also present a Proof of Concept (PoC) that uses L-PRISM to run multimedia SFCs. Our DSL and PoC were evaluated by software developers, and the results show that adopting L-PRISM facilitates the definition and deployment of multimedia SFCs based on multimedia VNFs.